(3Yhf Cgd GdLgGO ef GdCeQGA hGdCLfGOs ((3eMeO GdOehTi s)
(3ChdgG (B:s
(3CeG HYO , aEfi de BRd HYO eG hgH Gddg di ef GdeYQaI HBdGJ GdaQhSjI hObI GdfXQ hTOg GdaMU s
(3BNQgG (B:s
(3GdhGSYI ecGMdg GdLQF ebOeg hGddg Gdehab s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs